Efficient methods for energy saving in smart homes through breakdown the energy consumption - singh, Mayank; M. Srivastava, Viranjay (International Journal of Engineering and Technology, 2019)
The most crucial issue that affects the consumers, and environment is energy saving. Various home appliances are the primary con-cern in energy savings due to high-energy demand by these appliances. Smart home technologies are a good alternative for energy saving, and comfort for household devices. Buildings (structure and window direction) contribute significantly to overall energy consumption. Studies suggest that providing occupants with energy breakdown per-appliance energy consumption can help to save nearly 15% of energy. However, there are weak practical solutions are present to provide an energy saving breakdown. Current re-search requires hardware in each home and thus cannot be scaled across all households. In this research work, we have presented the techniques for producing energy breakdown in a home without requiring any additional sensing. Therefore, to identify the ener-gy breakdown, we have categorized the appliances in the different classes, i.e., switched-mode based power supply (SMPS), purely resistive, thermostatically controlled, etc. We are proposing a technique for the development of smart appliances that incorporate actuation capabilities and local intelligence for optimal appliance operation. With this proposed approach, the control and knowledge are pushed increasingly to the end device. This proposed approach has been applied to 287 homes from the data set available publically, in which the energy consumption measurement is based on individual home appliances. We have analysed the learned potential factors and found that the energy breakdown performance can improve using the static household properties. These proposed methods are scalable and approximately 42% more accurate compared to the state-of-the-art energy breakdown techniques.
Keywords: Energy Consumption; Smart Home; Domestic Appliances; Switched-Mode Power Supply; Energy Reliably; Energy Efficiency.